Military saints in Byzantium and Rus, 900-1200 - White, Monica, 1976- (Cambridge : Cambridge University Press, 2013)
"The rulers of the Byzantine Empire and its commonwealth were protected both by their own soldiers and by a heavenly army: the military saints. The transformation of Saints George, Demetrios, Theodore and others into the patrons of imperial armies was one of the defining developments of religious life under the Macedonian emperors. This book provides a comprehensive study of military sainthood and its roots in late antiquity. The emergence of the cults is situated within a broader social context, in which mortal soldiers were equated with martyrs and martyrs of the early Church recruited to protect them on the battlefield. Dr White then traces the fate of these saints in early Rus, drawing on unpublished manuscripts and other under-utilised sources to discuss their veneration within the princely clan and their influence on the first native saints of Rus, Boris and Gleb, who eventually joined the ranks of their ancient counterparts"--
Machine generated contents note: Introduction; 1. The prehistory of the military saints; 2. The formation of the martyr-warrior ideal; 3. The collective cult of the military saints; 4. The military saints in early Rus; 5. Boris and Gleb and the martyr-warrior ideal in Rus; 6. Military saints under the House of Suzdal; Conclusion; Appendix 1. Feast days of the principal military saints; Appendix 2. Reigns of Byzantine emperors mentioned in the text; Appendix 3. Simplified genealogy of the Riurikids; Appendix 4. Rus churches and monasteries dedicated to patronal figures; Appendix 5. Rus churches and monasteries dedicated to non-patronal figures.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Christian patron saints -- Cult -- Byzantine Empire; Christian martyrs -- Cult -- Byzantine Empire; Byzantine Empire -- History, Military -- 1081-1453.; Byzantine Empire -- Church history; Byzantine Empire. -- Stratos; War -- Religious aspects -- Christianity -- History of doctrines -- Middle Ages, 600-1500.; HISTORY / Europe / Eastern; RELIGION / Christianity / History; Electronic books